Efek Analgetik dan Penurunan Kadar Asam Urat Penderita Rheumatoid Arthritis dengan Terapi Komplementer Menggunakan Serai Merah - Muhammad Syahwal; Aluddin Aluddin (LPPM Hang Tuah Pekanbaru, 2023)
Increased levels of uric acid as a natural antioxidant are characterised by complaints of pain accompanied by joint swelling with acute symptoms and repeated attacks. One of the plants that is useful for reducing joint pain and swelling is red lemongrass (Cymbopogon nardus L. Randle). This study aims to analyze the effect of complementary therapy by soaking the feet with a mixture of red lemongrass as an analgesic and reducing uric acid levels in rheumatoid arthritis patients. This research method is pre-experimental with a one-group pre-test and post-test design without a control group on 23 elderly people. The results of the Wilcoxon non-parametric test showed that there was a change in pain scale and uric acid levels after the intervention (p = 0.00 and p = 0.02). It was concluded that warm water bath therapy with a mixture of red lemongrass was effective in reducing pain scale and reducing uric acid levels in rheumatoid arthritis patients.